Environmental education research in Indonesian Scopus indexed journal: A systematic literature review - H. Husamah; Hadi Suwono; Hadi Nur; Agus Dharmawan (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
Studies in the field of environmental education need to be continuously promoted in line with the increasing number of environmental problems. The purpose of this systematic literature review (SLR) was to review and compare investigations of researches on articles published by one Indonesian Scopus Indexed journal i.e., Jurnal Pendidikan IPA Indoneia (JPII) so that they are expected to have significant contributions to the topic of environmental education. This systematic literature review adopts five-step guidelines. The study standards that meet the requirements were as follows: (1). The data used were from the 2012-2021 publication year; (2) articles published in English; (3) Full paper can be accessed; (4) related to the theme of environmental education.  It can be concluded that JPII is a pro-environment education journal. JPII publishes 26 articles related to the theme of environment education. The most frequently used keywords were environmental education and students. JPII's important contribution in the theme of environmental education is to provide a real example of the implementation of SETS and to emphasize that the success of implementing environmental education depends on the models, methods, techniques, and tools that are continuously developed by experts.